A new species of Arachnopsita (Orthoptera: Grylloidea: Phalangopsidae) from caves in Guatemala - Junta, Vitor Gabriel Pereira; Castro-Souza, Rodrigo Antônio; Ferreira, Rodrigo Lopes (Zootaxa, 2022)
The current work presents the description of a new species for the genus Arachnopsita Desutter-Grandcolas & Hubbell, 1993 from caves in the municipality of Raxruhá, Alta Verapaz, Guatemala. The morphology of the phallic complex was used as the main criterion for distinguishing the species. In addition, we present the additional description for Arachnopsita cavicola (Saussure, 1897) and Arachnopsita uncinata Desutter-Grandcolas, 1997 from a new analyzed material. Finally, we present some ecological remarks for all the studied species as well as a brief discussion on troglomorphic traits for the genus.